Citizenship : the rise and fall of a modern concept - Fahrmeir, Andreas 1969- (Yale Univ. Press, 2007)
"This meticulously researched study provides a much-needed historical perspective on contemporary debates about immigration and the nature of citizenship. By tracing the origins of citizenship in four Western countries - Britain, France, Germany and the United States - from c. 1700 to the present, Andreas Fahrmeir demonstrates the contingency and changeability of the concept